“How can you advocate for something that is nonexistent?” (CM16-17) Power of community in a pandemic and the evolution of community-led response within a COVID-19 CICT and testing context - Hoffman, Sarah J.; Garcia, Yesenia; Altamirano-Crosby, Julieta; Ortega, Sarait M.; Yu, Kimberly; Abudiab, Seja M.; de Acosta, Diego; Fredkove, Windy M.; Karim, Sayyeda; Mann, Erin; Thomas, Christine M.; Yun, Katherine; et al. (Frontiers in Public Health, 2022)
Formal and informal bilingual/bicultural organizations and networks form the backbone of support for refugee, immigrant, and migrant (RIM) communities in the United States. They are pivotal in mitigating barriers and inequities in social and structural determinants of health. These organizations and networks are situated within the communities they serve, and often are established and run by members of a community, to serve the community. In the United States, the COVID-19 pandemic surfaced and widened existing health inequities for some racial and ethnic communities. Our primary objectives were to: (1) describe the processes that underpinned the pivotal role of immigrant-serving community structures in developing and implementing culturally sustaining programming in the context of pandemic response, and (2) amplify the voices of community experts, as they shared experiences and perspectives around these humanistic and community-centered approaches. We applied a community case study approach to a national sample of RIM-serving community structures representing broad country/region-of-origin, cultural, and linguistic identities. Community engagement strategies utilized in the project period included engaging community partners to identify and facilitate connections, and consult on analysis and dissemination. The project team conducted 20 in-depth, semi-structured interviews with a purposive sample of community experts/community organizations. Sampling strategy was further informed by immigrant identity (i.e., characterization of status) and geography (i.e., United States Department of Health & Human Services, Office of Intergovernmental and External Affairs Regions). Through thematic analysis, results identified key contextual, process-, and impact-oriented themes inherent to community-led COVID-19 responses, that were situated within and around the public and health system response to the pandemic. As public health and health systems scrambled to address acute and unprecedented barriers to access, distribution of COVID-19-related health resources and services, and disparate health outcomes, community structures diligently and intentionally reimagined and reconceptualized their response to COVID-19, frequently in the setting of scarce resources. The grassroots response evolved as a counter-narrative to top–down equity processes, historically defined by systems and applied to the community.